Suprafascial application of Vancomycin powder in the operation of posterior instrumental fusion for the prevention of local infectious complications - I. A. Stepanov; V. A. Beloborodov; M. A. Shameeva (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Surgical site infections (SSIs) are one of the most serious adverse events that develop in patients after performing an operation of instrumental spinal fusion. A search of literary sources in various databases showed the presence of isolated studies devoted to studying the effectiveness of suprafascial local application of Vancomycin powder after performing an operation of posterior instrumental spinal fusion in preventing the development of SSIs. At the same time, the results of these studies are ambiguous and in many ways contradictory.The OBJECTIVE of this study was to study the effectiveness of the suprafascial local application of Vancomycin powder after performing the operation of the posterior instrumental spinal fusion in preventing the development of SSIs, and also to identify the main adverse drug reactions in the local use of this antibacterial drug.METHODS AND MATERIALS. The study included medical records of 219 patients who underwent surgery for posterior instrumental spinal fusion on the cervical, thoracic, and lumbosacral spine for various pathological conditions. Medical records of patients are divided into two groups: group I (comparison group) – 113 patients who used the standard protocol of prophylaxis of SSIs and group II (main group) – 106 patients who used the standard protocol of prophylaxis of SSIs in combination with suprafascial local use of Vancomycin powder. The analysis of the frequency of occurrence of SSIs after the operation of the posterior instrumental spinal fusion in the studied groups of respondents and the prevalence of undesirable medicinal phenomena in the case of local suprafascial application of Vancomycin powder was performed.RESULTS. The prevalence of SSI after posterior instrumental spinal fusion in the control group of patients was 4.2 %. At the same time, in the main group of patients, where the standard protocol was used in combination with suprafascial local use of Vancomycin powder for the purpose of prophylaxis of SSIs, there were no cases of SSIs development. We have not revealed any adverse drug reactions when using Vancomycin powder in patients of the main group.CONCLUSION. The local use of Vancomycin powder in patients after posterior instrumental spinal fusion is an effective and safe method of preventing the development of SSIs.